Hubungan Dukungan Sosial Rekan Kerja Dengan Stres Kerja (Studi pada Pekerja di PT X) - Permatasari, Aisyah (Jurnal Ilmu Kesejahteraan Sosial, 2025)
Workers are vulnerable to work-related stress due to job demands, time constraints, and limited leisure time, leading to psychological issues such as anxiety related to their work. In the context of social welfare studies, job stress affects overall workers’ well-being and disrupts their social functioning in the workplace. Social support from coworkers is potentially reduce stress in workplace, which is crucial for creating organizational well-being. It also helps workers improve job engagement, cope with fatigue, and manage stress. This study examined the relationship between social support from coworkers and job stress among 90 employees at PT X. It used a quantitative method with accidental sampling for data collection. The analyses present univariate and bivariate analysis using Kendall's tau-b correlation test. It found that 73.3% of 66 respondents experience moderate job stress, and 72.2% consisting of 65 receive moderate social support from coworkers. The correlation coefficient between coworker support and work stress was -0.260. It concluded that the strength of the relationship is weak but has a negative relationship, meaning that higher coworker support is associated with lower work stress.